2021
DOI: 10.3390/ani11102842
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nano-Bromocriptine on Egg Production Performance and Prolactin Expression in Layers

Abstract: The current study aimed to investigate the potential use of nano-bromocriptine in improving the laying performance of late laying hens by modulating the prolactin gene expression. A total of 150 NOVOgen brown laying hens aged 70 weeks were randomly allocated into three groups of 50 birds each. The first group was kept as a control, while the second and the third groups were treated with bromocriptine and nano-bromocriptine, respectively, at a dose of 100 µg/kg body weight per week. The pause days, egg producti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The current results may be similar to those of Rangneker et al (1978) and Lopez et al (1996) who explained that during incubation, granules and cells in the cephalic lobe grow, which raises prolactin levels in the blood. Prolactin levels decreased after antiprolactin or neutralization treatments performed by Parvez et al (2017), and Dawod et al (2021), who also concluded that prolactin levels are high during the incubation period. These findings may compare with the current findings because layers take fewer breaks than the broilers being studied.…”
Section: Resultsmentioning
confidence: 91%
“…The current results may be similar to those of Rangneker et al (1978) and Lopez et al (1996) who explained that during incubation, granules and cells in the cephalic lobe grow, which raises prolactin levels in the blood. Prolactin levels decreased after antiprolactin or neutralization treatments performed by Parvez et al (2017), and Dawod et al (2021), who also concluded that prolactin levels are high during the incubation period. These findings may compare with the current findings because layers take fewer breaks than the broilers being studied.…”
Section: Resultsmentioning
confidence: 91%